Reaction Kinetics of Cinnamaldehyde Hydrogenation over Pt/SiO2: Comparison between Bulk and Intraparticle Diffusion Models - Ali Al-Shathr; Zaidoon M. Shakor; Bashir Y. Al-Zaidi; Hasan Sh. Majdi; Adnan A. AbdulRazak; Safa Aal-Kaeb; Adel A. Shohib; James McGregor (International Journal of Chemical Engineering)
The liquid-phase hydrogenation of cinnamaldehyde over a Pt/SiO2 catalyst was investigated experimentally and theoretically. The experiments were conducted in a 300 cm3 stainless steel stirred batch reactor supplied with hydrogen gas and ethanol as a solvent. Five Langmuir–Hinshelwood kinetic models were investigated to fit the experimental data. The predictions from the bulk model were compared with predictions from the intraparticle diffusion model. Competitive and non-competitive mechanisms were applied to produce the main intermediate compound, cinnamyl alcohol. Reaction rate parameters for the different reaction steps were calculated by comparing between the experimental and mathematical models. All rate data utilized in the present study were obtained in the kinetic regime. The kinetic parameters were obtained by applying a nonlinear dynamic optimization algorithm. Nevertheless, the comparison between the methodology of the present model and these five models indicated that the non-competitive mechanism is more acceptable and identical with the single-site Langmuir–Hinshelwood kinetic model including mass transfer effects and it mimicked the reactant behavior better than the other models. In addition, the observed mean absolute error (MAE) for the non-competitive mechanism of the present model was 2.3022 mol/m3; however, the MAE for the competitive mechanism was 2.8233 mol/m3, which is an increase of approximately 18%. The prediction of the intraparticle diffusion model was found to be very close to that of the bulk model owing to the use of a catalyst with a very small particle size (<40 microns). Employing a commercial 5% Pt/SiO2 catalyst showed a result consistent with previous research using different catalysts, with an activation energy of ≈24 kJ/mol.